Book Review: Capital, State, Empire: The New American Way of Digital Warfare by Scott Timcke - Marc Kosciejew (tripleC: Communication, Capitalism & Critique)
Marc Kosciejew reviews Capital, State, Empire: The New American Way of Digital Warfare by Scott Timcke (2017; London: University of Westminster Press [ISBN: 978-1-911534-36-5]).